PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN DENGAN MENGGUNAKAN PENDEKATAN CONSTRUKTIVISME DI KELAS IV SDN 38 API-API KECAMATAN BAYANG - HARNI ATI (FKIP UMSB, 2017)
Planning learning reading comprehension using cosntruktivisme approach manifested in a lesson plan prepared in accordance with step-by-step approach construktivisme. Implementation of learning reading comprehension using construktivisme approach consists of early learning activities, the core activity of learning that includes the step prabaca, saatbaca, and pascabaca, and the final activity of learning. Implementation of learning reading comprehension using construktivisme approach implemented by the steps of: a) orientation, b) elicitation, c) restructuring ideas, d) the use of the idea in many situations, and (e) review. Assessment of learning in reading comprehension approach construktivisme do with the assessment process and assessment of results. Assessment process as affective and psychomotor. While the results in the form of cognitive assessment. Assessment of learning reading comprehension using construktivisme approach in which the first cycle has increased the average results of the assessment process, namely 73.2 and 44.4% Kentuntasan. while in the second cycle the average results of the assessment process, namely 81.1 and 88.9% completeness. Keywords: reading, approach construktivisme